1996
DOI: 10.1200/jco.1996.14.2.549
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary cutaneous B-cell lymphomas of follicle center cell origin: a clinical follow-up study of 55 patients treated with radiotherapy or polychemotherapy.

Abstract: Both RT and CHOP PCT are highly effective modes of treatment for PCFCCL. In localized PCFCCL, RT is the treatment of choice. In patients with multiple tumors involving anatomic nonrelated parts of the skin, CHOP rather than COP PCT is the preferred mode of treatment. PCFCCL on the lower legs, a subgroup that characteristically occur in elderly patients, have a higher relapse rate and a less favorable prognosis than PCFCCL presenting on the head or trunk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(58 citation statements)
references
References 4 publications
4
48
1
5
Order By: Relevance
“…EFS at 5 years was at 60% for patients with localized disease vs 20% for those with diffuse disease (P Ͻ 0.01). In contrast to a previous report, 8 the prognosis for patients with PCLL of the B cell type localized on the leg was not poor in our series; however, this discrepancy may be explained by the fact that all our patients received chemotherapy and the patient population was small. Under polychemotherapy, these patients had a relapse rate of 50%, which is lower than the relapse rate observed after radiation therapy alone or monochemotherapy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…EFS at 5 years was at 60% for patients with localized disease vs 20% for those with diffuse disease (P Ͻ 0.01). In contrast to a previous report, 8 the prognosis for patients with PCLL of the B cell type localized on the leg was not poor in our series; however, this discrepancy may be explained by the fact that all our patients received chemotherapy and the patient population was small. Under polychemotherapy, these patients had a relapse rate of 50%, which is lower than the relapse rate observed after radiation therapy alone or monochemotherapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients have been given various regimens from monochemotherapy to polychemotherapy or radiation therapy alone or associated with chemotherapy and experienced high relapse rates. [6][7][8] However, recent results have suggested that PCLL of the B cell type should not be treated with radiation therapy alone. 8 The use of polychemotherapy in this setting and results observed in nodal large-cell non-Hodgkin's lymphomas 8,14 led us to include PCLL patients in a protocol of polychemotherapy for high-grade lymphomas (LNH87).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Piccinno et al [13] found a relapse rate of 68% following radiotherapy alone. In our study, excisional surgery was found to have a relapse rate of at least 50% in both DLBCL and MZL.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chemotherapy has also been used widely in the treatment of PCBCL [4,10,11,13,15,16]. The most appropriate form of chemotherapy is not known, but CHOP has been found to be superior to COP (cyclophosphamide, vincristine, prednisolone) in some studies [13,[17][18][19]. This form of therapy has traditionally been used for patients with multifocal or extensive lesions as they are considered to be at higher risk of developing extracutaneous disease [11,16].…”
Section: Discussionmentioning
confidence: 99%